CHARACTERISTICS OF PARTICLES PRODUCED IN HADRON-NUCLEUS COLLISIONS - Ahmad, Tufail (JOURNAL OF ADVANCES IN PHYSICS, 2014)
A detailed study on mean multiplicities of secondary charged particles is presented. The average number of grey, black and heavy particles are found to be independent of energy in proton-nucleus interactions whereas for pion-nucleus collisions the data deviates from its independence with energy. The ratio of mean number of charged particles produced in pion-nucleus collisions to its number in proton-nucleus interactions at almost the same energy is found to be similar at different energies.